أسلمة المعرفة وجهودها لتحييد فكرة الإسلام الليبرالي: دراسة وصفية : The Islamization of Knowledge and Its Efforts to Neutralize The Idea of Liberal Islām: A Descriptive Study - Ibnu Hudzaifah Hamka; Rahmah Binti Ahmad H. Osman; Mohd Norhan bin Hamsi; Muhammad Hafiz bin Muhammad Zain (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
ملخص تتناول هذه الدراسة من الصراع بين أسلمة المعرفة وليبرالية الإسلام. ضرورة مشروع أسلمة المعرفة إلى التزكية من التأثيرات والعناصر الغربية في الفكر والعلوم الإنسانية لأنها لا تناسب بالنظر العالمي الإسلامي. وأصبحت ظاهرة الإسلام الليبرالي تحديًا من تحديات أسلمة المعرفة للوصول إلى أغراضها. تهدف الدراسة إلى عرض الجهود التي قد تم فعلها لتحييد فكرة الإسلام الليبرالي. قامت الدراسة على المنهج الوصفي من خلال دراسة المفهوم عن أسلمة المعرفة والإسلام الليبرالي وتتبع التاريخ منهما في إندونيسيا وماليزيا. ومن نتائج الدراسة: استنتج الباحثون أنّ أسلمة المعرفة قد بذلت جهدها في شتى الأنشطة لتطبيق التحييد من العناصر التي تتأثر من النظر العالمي الغربي في العلم والفكر عاما. وكانت الأنشطة أغلبها تدور في الأنشطة التحريرية والنشرية، والمناقشات والحاضرات والمناظرات العلمية، وتأسيس المؤسسات أو المنظمات الاجتماعية والعلمية. Abstract This study deals with the conflict between the Islamization of knowledge and the liberalism of Islam. The necessity of the project of Islamization of knowledge is to be purifying from Western influences and elements in thought and human sciences because they do not suitable the Islamic world view. The phenomenon of liberal Islam became one of the challenges of Islamization of knowledge to reach its goals. The study aims to present the efforts that have been made to neutralize the idea of liberal Islam. The study was based on the descriptive approach by studying the concept of Islamization of knowledge and liberal Islam and tracing the history of them in Indonesia and Malaysia. From the results of the study: The researchers concluded that the Islamization of knowledge project has exerted its efforts in various activities to implement the neutralization of the elements that are affected by the Western world view in science and thought generally. Most of the activities revolved around editorial and publishing activities, discussions, lectures and scientific debates, and the establishment of social and scientific institutions or organizations.